Study on the Detection of Dairy Cows' Self-Protective Behaviors Based on Vision Analysis. (10th October 2018) - Li, Jia; Wu, Pei; Kang, Feilong; Zhang, Lina; Xuan, Chuanzhong
Abstract : The study of the self-protective behaviors of dairy cows suffering dipteral insect infestation is important for evaluating the breeding environment and cows' selective breeding. The current practices for measuring diary cows' self-protective behaviors are mostly by human observation, which is not only tedious but also inefficient and inaccurate. In this paper, we develop an automatic monitoring system based on video analysis. First, an improved optical flow tracking algorithm based on Shi-Tomasi corner detection is presented. By combining the morphological features of head, leg, and tail movements, this method effectively reduces the number of Shi-Tomasi points, eliminates interference from background movement, reduces the computational complexity of the algorithm, and improves detection accuracy. The detection algorithm is used to calculate the number of tail, leg, and head movements by using an artificial neural network. The accuracy range of the tail and head reached [0.88, 1] and the recall rate was [0.87, 1]. The method proposed in this paper which provides objective measurements can help researchers to more effectively analyze dairy cows' self-protective behaviors and the living environment in the process of dairy cow breeding and management.